Labor market consequences of antitax avoidance policies - Katarzyna Bilicka (W.E. Upjohn Institute for Employment Research, 2021)
In this paper, I analyze the local labor market consequences of multinational firms reallocating employees across their affiliates in response to antitax avoidance policies. I leverage the introduction of a worldwide debt cap in 2010 in the United Kingdom as a quasi-natural experiment that limited one of the forms of profit shifting - debt shifting - for a group of multinational corporations (MNCs). Multinationals affected by the reform reallocated their employees from the United Kingdom to foreign locations. This affected London-based service sector firms the most. I show that this led to a reduction in the number of jobs available in regions exposed to the reform in the United Kingdom. In foreign countries, the initial reallocation of labor across firms resulted in a much larger expansion of the affected local labor markets. These results suggest that a reallocation of labor across firms generates asymmetries in how negative and positive firm-level shocks are amplified through regional markets.
Keywords: H25; H26; 330; Debt shifting; multinational companies; local labor markets